Development Of An Immunocontraceptive Vaccine For Biocontrol Of Rats - Lai, Kit Yee (2004)

(untitled)
Zona pellucida (ZP) is an extracellular matrix that surrounds the mammalian oocyte. The rat ZP is composed of three major glycoproteins: ZP1, ZP2 and ZP3. As a primary sperm receptor, ZP3 has been utilised as an immunogen to prevent fertilisation of the ovum. Unfortunately, the availability of ZP3 protein is always limited and purified protein is not available. DNA vaccination is therefore an excellent alternative. ZP3 cDNA was amplified from R. rattus diardii ovary as a first step towards the development of ZP3-based DNA vaccine. The ZP3 gene has an open reading frame of 1272 nucleotides encoding a polypeptide of 424 amino acid residues which shares 87% identity with mouse homologue. The anti-fertility polynucleotide vaccine was generated by placing ZP3 gene into a mammalian plasmid expression vector. Plasmid containing the entire ZP3 gene sequence was designated pcDNA/1300. Meanwhile, constructs pcDNA/720 and pcDNA/580 comprised partial ZP3 gene encoding the N-terminal and C-terminal half of the protein respectively. In vitro transfection of mammalian cells with these plasmids DNA led to their cytosolic expression. Sperms were attracted and bound to cells harbouring pcDNA/1300 and pcDNA/580 because these two constructs encoded the sperm-combining sites of ZP3. Administration of these DNA vaccines resulted in vivo expression of ZP3 protein, which in turn stimulates specific cellular and humoral immune responses directed against self-ZP3 protein bearing cells or oocytes. Lacking or destruction of such cells resulted in an effective contraception in female animals. The ovarian dysfunction was characterised by excessive depletion of follicles and an increase in the number of oocyte-free cell clusters. The integrity of most follicles was challenged, as it was significantly infiltrated by immune cells. These ZP3 specific immune cells were shown to be a mixture of CD4+ and CD8+ T-lymphocytes subsets. Alterations in ovarian function were also evidenced when vaccinated animals were no longer sensitive to an intensive exogenous hormonal (hCG) treatment. Among the three constructs, pcDNA/1300 is the most effective contraceptive vaccine followed by pcDNA/580. The reduction in average litter size achieved by pcDNA/1300 was >90%. It is an excellent irreversible contraceptive vaccine as none of the vaccinated rats showed signs of recovery after three injections. In contrast, rats vaccinated with pcDNA/580 regained fertility over an extended period. On the other hand, vaccination with pcDNA/720 construct has no significant impact on rat fertility. Hence, special attention was given to pcDNA/1300. In DNA vaccination, the role of cell-mediated immune response was pre-eminent as the titre of ZP3-antibody produced was significantly low. Relatively, vaccination with recombinant ZP3 protein expressed by yeast cells, P. pastoris stimulated strong antibody response, but no correlation between antibody titres and infertility was observed. Similarly, when the cytokines IL-4 gene was co-immunised along with pcDNA/1300, a dramatic increase in ZP3 antibody level did not enhance the efficacy of pcDNA/1300. Indeed by driving the immune response of pcDNA/1300 towards Th2 direction, this weakened its effectiveness in preventing fertilisation. Construct pHumoral-ZP3 was assembled as an attempt to improve the potency of pcDNA/1300. Modification of pcDNA/1300 with viral NP conjugation produced a significant enhancement on the levels of ZP3 antibody. The magnitude of the antibody response was comparable to that generated through the use of cytokine genetic adjuvant, IL-4. However, despite high ZP3 antibody titres, rats vaccinated with pHumoral-ZP3 produced normal litter size. This study demonstrated the application of a ZP3-based DNA vaccine in fertility control. The results obtained are extremely encouraging for the development of a vaccine for lasting rat population control. Meanwhile, the current DNA construct serves as excellent model for the generation of similar vaccines to prevent individual animals from conceiving. As a result, the expensive and complicated invasive procedures like surgery and castration can be avoided.